CsPbX3 (X = Br, I) perovskite quantum dot embedded low-melting phosphosilicate glasses: controllable crystallization, thermal stability and tunable emissions. Issue 25 (20th June 2018) - Chen, Daqin; Yuan, Shuo; Chen, Xiao; Li, Junni; Mao, Qinan; Li, Xinyue; Zhong, Jiasong
Abstract : CsPbX3 (X = Br, I) QD embedded glasses are fabricated via a glass crystallization strategy, exhibiting tunable luminescence and superior thermal stability. Abstract : In this work, low-melting (700 °C) phosphosilicate glasses embedded with CsPbX3 (X = Br, I) perovskite quantum dots (QDs) were fabricated via a glass crystallization strategy. The as-prepared CsPbBr3 QDs@glass nanocomposites exhibited typical green luminescence assigned to exciton recombination radiation and outstanding thermal stability due to the protection of the robust inorganic glass host. Multi-color tunable emissions in the spectral range of 500–750 nm were achieved by modifying the molar ratio of halide sources in the glass. As a proof-of-concept experiment, a light-emitting diode device was constructed by coupling the green-emitting CsPbBr3 QDs@glass and red-emitting CsPbBr2 I QDs@glass with a commercial InGaN blue chip, yielding a bright white light emission with excellent optoelectronic performance. It is expected that the investigated CsPbX3 QDs@glass nanocomposites may find promising application as color converters in solid-state-lighting.